Ketubah Ortakoy. - Trena, Shelomoh; Trena, Mazal Ṭov; Rosanes, Yehudah; Garo, Yitsḥaḳ; Hebrew Manuscripts (Columbia University Libraries) (1850)
A ketubah, Jewish traditional marriage contract, from Ortakoy, Turkey, written on Tuesday, 19th of Elul 5610 [Aug. 27, 1850].
Manuscript written on paper in Oriental script.
An arch frames the text. It is surrounded by abundant vegetal tendrils.
Digital version available with no restrictionsUnrestricted online accessstarNNC
A ketubah, Jewish traditional marriage contract, from Ortakoy, Turkey, written on Tuesday, 19th of Elul 5610 [Aug. 27, 1850].
Also available on microfilm.
Keywords: Manuscripts, Hebrew. / fast / (OCoLC)fst01008360; Ketubah. / fast / (OCoLC)fst00986963; Jews. / fast / (OCoLC)fst00983135; Manuscripts, Hebrew / 19th century.; Ketubah / 19th century.; Turkey / Ortaköy (Çorum İli) / fast / (OCoLC)fst01325597; Ortaköy (Çorum İli, Turkey) / Jews / 19th century.